ANALISIS PREFERENSI PENGGUNAAN META ADS DAN GOOGLE ADS DALAM STRATEGI DIGITAL MARKETING DI HOTEL FOUR POINTS BY SHERATON BALI UNGASAN - Asa, Kadek; Andayani, NL Henny; Mahardika, A A Ngurah Yudha Martin (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the preference for using digital advertising platforms, namely Meta Ads and Google Ads, by Four Points by Sheraton Ungasan Bali Hotel. In an increasingly competitive hospitality industry, digital marketing strategies are essential to improve hotel visibility and occupancy. This research applies a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation. The results indicate that the hotel prefers Meta Ads due to its ability to target audiences more specifically, cost efficiency, flexibility in visual content, and its impact on brand awareness. Meanwhile, Google Ads has not been optimally utilized due to limitations in management and platform understanding. These findings demonstrate that Meta Ads significantly contribute to the effectiveness of the hotel's digital marketing campaigns.